Sanguiin H-6 Fractionated from Cloudberry (Rubus chamaemorus) Seeds Can Prevent the Methicillin-Resistant Staphylococcus aureus Biofilm Development during Wound Infection - Aguilera-Correa, John Jairo; Fernandez-Lopez, Sara; Cunas-Figueroa, Iskra Dennisse; Perez-Rial, Sandra; Alakomi, Hanna-Leena; Nohynek, Liisa; Oksman-Caldentey, Kirsi-Marja; Salminen, Juha-Pekka; Esteban, Jaime; Cuadros, Juan; Puupponen-Pimia, Riitta; Perez-Tanoira, Ramon; et al. (Antibiotics, 2022)
Staphylococcus aureus is the most common cause of surgical site infections and its treatment is challenging due to the emergence of multi-drug resistant strains such as methicillin-resistant S. aureus (MRSA). Natural berry-derived compounds have shown antimicrobial potential, e.g., ellagitannins such as sanguiin H-6 and lambertianin C, the main phenolic compounds in Rubus seeds, have shown antimicrobial activity. The aim of this study was to evaluate the effect of sanguiin H-6 and lambertianin C fractionated from cloudberry seeds, on the MRSA growth, and as treatment of a MRSA biofilm development in different growth media in vitro and in vivo by using a murine wound infection model where sanguiin H-6 and lambertianin C were used to prevent the MRSA infection. Sanguiin H-6 and lambertianin C inhibited the in vitro biofilm development and growth of MRSA. Furthermore, sanguiin H-6 showed significant anti-MRSA effect in the in vivo wound model. Our study shows the possible use of sanguiin H-6 as a preventive measure in surgical sites to avoid postoperative infections, whilst lambertianin C showed no anti-MRSA activity. Peer reviewed